The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ps.6580
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of zeylenone from Uvaria grandiflora as a potential botanical fungicide

Abstract: BACKGROUND: Botanical pesticides play an important role in organic agricultural practices and are widely used in integrated pest management (IPM). Uvaria grandiflora was mainly reported as traditional medicines and possessed antibacterial, antioxidant, and antiprotozoal activities. Therefore, important biological activities of U. grandiflora may suggest that they have the potential to be used as botanical pesticides.RESULTS: The extract of U. grandiflora exhibited broad-spectrum inhibitory activity toward phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Then, the mycelia were sampled and ground into powder under liquid nitrogen for the determination of sugar, lipid and triglyceride content. The content of sugar and lipid in S. rolfsii was determined using DNS method 13 and phosphovanillin method, 41 respectively. The triglyceride content in mycelia was measured using a Triglyceride Assay Kit (Nanjing Jiancheng Bioengineering Research Institute, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the mycelia were sampled and ground into powder under liquid nitrogen for the determination of sugar, lipid and triglyceride content. The content of sugar and lipid in S. rolfsii was determined using DNS method 13 and phosphovanillin method, 41 respectively. The triglyceride content in mycelia was measured using a Triglyceride Assay Kit (Nanjing Jiancheng Bioengineering Research Institute, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Pyruvate content, ATP content and mitochondrial membrane potential are important indicators of mitochondrial functions. 13,42,43 The pyruvate and ATP content of S. rolfsii mycelia after treatments with butylidenephthalide (0, EC 50 and EC 85 ; www.soci.org K Cui et al…”
Section: Pyruvate Atp Content and Mitochondrial Membrane Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors speculated that the bioactive peptides are the components of programmed or induced proteolysis of plant proteins, which can realize secondary antimicrobial functions. Potted plant experiments conducted by He et al 94 . indicated that both microemulsion of Uvaria grandiflora extract and its secondary metabolite zeylenone display excellent control efficacies against tomato late blight.…”
Section: Chemical Compounds From Plantsmentioning
confidence: 99%
“…Plants are a potential source of natural compounds with environmentally nonpersistent and low toxicity 20 . Finding antifungal natural compounds from environmentally safe biodegradable plant sources and using them as the lead compounds of new botanical fungicides is one of the feasible strategies to reduce the use of chemical fungicides 21–23 . Many species of plants have been reported to have effects against plant pathogenic fungi, 24 Such as Polygonum cuspidatum (Polygonaceae), 25 Thymus vulgaris (Lamiaceae), 26 Allium sativum (Liliaceae), 27 Cnidium monnieri (Umbelliferae), 28 Syzygium aromaticum (Myrtaceae) 29 and Carpesium macrocephalum (Asteraceae) 30…”
Section: Introductionmentioning
confidence: 99%